Repression of Virus-Induced Interferon A Promoters by Homeodomain Transcription Factor Ptx1 - Lopez, Sébastien (American Society for Microbiology, 2000)
Interferon A (IFN-A) genes are differentially expressed after virus induction. The differential expression of individual IFN-A genes is modulated by substitutions in the proximal positive virus responsive element A (VRE-A) of their promoters and by the presence or absence of a distal negative regulatory element (DNRE). The functional feature of the DNRE is to specifically act by repression of VRE-A activity. With the use of the yeast one-hybrid system, we describe here the identification of a specific DNRE-binding protein, the pituitary homeobox 1 (Ptx1 or Pitx1). Ptx1 is detectable in different cell types that differentially express IFN-A genes, and the endogenous Ptx1 protein binds specifically to the DNRE. Upon virus induction, Ptx1 negatively regulates the transcription of DNRE-containing IFN-A promoters, and the C-terminal region, as well as the homeodomain of the Ptx1 protein, is required for this repression. After virus induction, the expression of the Ptx1 antisense RNA leads to a significant increase of endogenous IFN-A gene transcription and is able to modify the pattern of differential expression of individual IFN-A genes. These studies suggest that Ptx1 contributes to the differential transcriptional strength of the promoters of different IFN-A genes and that these genes may provide new targets for transcriptional regulation by a homeodomain transcription factor.